Kontribusi Kecepatan Dan Kelincahan Terhadap Keterampilan Dribbling Bola Pada Peserta Ekstrakurikuler Futsal SMP PGRI Pekanbaru - Pohan, M.Hashabul Kahfi; Fernando, Ricky (Jurnal Pendidikan, Sains Dan Teknologi, 2024)
The aim of this research is to determine the contribution of speed and agility to ball dribbling skills in futsal extracurricular participants at PGRI Pekanbaru Middle School. This type of research is multiple correlation. The population in this study were 15 futsal extracurricular students at PGRI Pekanbaru Middle School. The sampling technique used was total sampling so that the sample in this study was 15 people. The research instruments used were the 30 meter running test, shuttle run test and futsal ball dribbling test. The data analysis technique used is the multiple correlation value test and calculating the contribution value. Based on the results of the research that has been carried out, it can be concluded that: (1) There is a contribution of speed to ball dribbling skills in futsal extracurricular participants at PGRI Pekanbaru Middle School with a value of rcount = 0.642 > rtable = 0.514 and a KD value of 41.22%, (2) There is the contribution of agility to ball dribbling skills in PGRI Pekanbaru Middle School futsal extracurricular participants with a value of rcount = 0.751 > rtable = 0.514 and a KD value of 56.40%, (3) There is a contribution of speed and agility to ball dribbling skills in PGRI Pekanbaru Middle School futsal extracurricular participants with a value of rcount = 0.784 > rtable = 0.514 and a KD value of 61.47%.